Studies in Health Technology and Informatics Volume 5 - Christensen, Jens Pihlkjaer (IOS Press, 2014)
New technologies and recent findings in neuromotor control can provide useful tools to conceive new diagnosis procedures and to restore impaired motor functions. For this purpose the basic understanding of natural sensory-motor integration must be combined with the knowledge of neuromotor disorders and with the advanced technologies used in rehabilitation. This is an interdisciplinary problem that requires the contributions of different researchers working in complementary areas (neurophysiology, neurology, rehabilitation, bioengineering and advanced technology).